2011
DOI: 10.1039/c0mb00349b
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a high-affinity network of secretagogin-binding proteins involved in vesicle secretion

Abstract: Secretagogin is a hexa EF-hand Ca(2+)-binding protein expressed in neuroendocrine, pancreatic endocrine and retinal cells. The protein has been noted for its expression in specific neuronal subtypes in the support of hierarchical organizing principles in the mammalian brain. Secretagogin has previously been found to interact with SNAP25 involved in Ca(2+)-induced exocytosis. Here, the cellular interaction network of secretagogin has been expanded with nine proteins: SNAP-23, DOC2alpha, ARFGAP2, rootletin, KIF5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 42 publications
4
35
0
Order By: Relevance
“…Secretagogin is a Ca 2+ sensing protein that changes its conformation when [Ca 2+ ] i rises, allowing its interaction with exocytotic proteins like SNAP25 and Doc2alpha 29 . Accordingly, we observed that secretagogin interacts with tomosyn under basal conditions, and this is decreased in response to glucose and KCl, the latter finding suggesting an important role for [Ca 2+ ] i as opposed to glucose-dependent metabolic signals.…”
Section: Discussionmentioning
confidence: 99%
“…Secretagogin is a Ca 2+ sensing protein that changes its conformation when [Ca 2+ ] i rises, allowing its interaction with exocytotic proteins like SNAP25 and Doc2alpha 29 . Accordingly, we observed that secretagogin interacts with tomosyn under basal conditions, and this is decreased in response to glucose and KCl, the latter finding suggesting an important role for [Ca 2+ ] i as opposed to glucose-dependent metabolic signals.…”
Section: Discussionmentioning
confidence: 99%
“…Its tertiary structure changes upon Ca 2+ -binding [55]. This property, together with an in vitro -identified cellular interaction network [57], suggests that secretagogin may act as a Ca 2+ sensor rather than buffer in neurons. This review summarizes experimental and histopathological data hitherto obtained and concerned with secretagogin's structure, expression pattern, physiological and pathological significance and discusses critical experiments to conclusively define secretagogin functions in the central nervous system (CNS).…”
Section: Introduction: Brief Overview Of Ca2+-binding Proteins Witmentioning
confidence: 99%
“…Here, we show that the supraoptic nucleus (nucleus decussationis supraopticae, pars ventralis) is densely packed with secretagogin + neurons with further cell groups present in the lateral hypothalamus, and paraventricular and infundibular nuclei. Since secretagogin was shown to impact vesicle secretion and release Bauer et al, 2011;Hasegawa et al, 2013], it is conceivable that secretagogin plays a role in the control of hypothalamic hormone secretion/release.…”
Section: + -Binding Proteinsmentioning
confidence: 99%
“…Given its relatively low Ca 2+ -binding affinity and conformational modifications upon Ca 2+ binding, secretagogin qualifies as a Ca 2+ sensor [Rogstam et al, 2007]. The predicted interactome of secretagogin includes members of SNARE (soluble NSF attachment protein receptor) superfamily of proteins, suggesting its involvement in regulating secretory and synaptic vesicle trafficking and activity-dependent release [Rogstam et al, 2007;Bauer et al, 2011;Hasegawa et al, 2013]. Secretagogin is expressed in essentially all organ systems [Wagner et al, 2000;Alpár et al, 2012].…”
Section: Introductionmentioning
confidence: 99%